Crucial images in the presentation of a Kurdish national identity : heroes and patriots, traitors and foes - Strohmeier, Martin (Social, economic, and political studies of the Middle East and Asia, 2003)
This work covers the discourse on Kurdishness and the development of the Kurdish national movement from its inception at the end of the 19th century to the late 1930s. It examines the efforts of aspiring Kurdish leaders to "awaken" their fellow Kurds to the necessity of the Kurdish cause.